Methodological problems of inventory and assessment of recreational and tourism potential - Sych, Vitaliy (Journal of Education, Health and Sport, 2017)
The article considers the concepts of recreational resources and recreational conditions and emphasizes that not all recreational conditions and resources can be estimated using quantitative assessment scales. In the case when public recreational goods do not have quantitative assessments, they use the methods of ranking or verbal attributive comparisons. The concept of natural capital is considered in the work, attention is paid to ecological and economic assessments of recreational conditions and resources, also to the participation of the technosphere in the functioning of recreational and tourism activities, ranking of natural resources according to their competitive properties. The directions of development of the methodological scheme of estimation of recreational conditions and resources taking into account modern theoretical and methodical developments of social and economic benefits are marked.